The altered hypothalamic network functional connectivity in diminished ovarian reserve and regulation effect of acupuncture: a randomized controlled neuroimaging study protocol - Gao, Feng; Yu, Yang; Wang, Fuwei; Fang, Yigong (Frontiers in Endocrinology, 2025)
Diminished ovarian reserve (DOR) is characterized by a decrease in the quantity and quality of oocytes, leading to reduced chances of natural conception and a poorer response to fertility treatments. Along with these reproductive challenges, DOR often causes psychological symptoms such as depression, anxiety, and sleep disturbances, which negatively affect overall well-being and quality of life. Acupuncture has been proposed as a promising complementary therapy for DOR, but the mechanisms through which it exerts its effects are not yet fully understood. This study aims to investigate the effects of acupuncture on ovarian function, psychological well-being, and the central nervous system in women with DOR. We will recruit 42 women with DOR and 21 healthy controls (HCs), randomly assigning DOR patients to receive either verum acupuncture (VA) or sham acupuncture (SA) for 12 weeks. Ovarian function will be assessed using Anti-Müllerian hormone (AMH), antral follicle count (AFC), and follicle-stimulating hormone (FSH). Psychological well-being will be evaluated using the Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), and Self-Rating Scale of Sleep (SRSS). To explore the neurological effects, resting-state functional connectivity (rsFC) of the hypothalamus will be assessed using functional magnetic resonance imaging (fMRI). This research aims to clarify how acupuncture affects the central nervous system, hormonal regulation, and ovarian function in women with DOR. The findings may provide valuable insights for developing evidence-based acupuncture protocols that can improve both reproductive outcomes and quality of life for women with DOR.